Possibilities of South Asian Sociology and Regional Imagining: In Conversation with two Nepali Sociologists - Sarkar, Swatahsiddha (Nepal Journal of Sociology, 2024)
This interview explores the feasibility of envisioning South Asian sociology as a distinct academic scholarship, stemming from the collaborative attempts among sociologists from South Asia. It assesses this proposal by probing the current academic landscape and incorporating perspectives from two leading sociologists affiliated with the Central Department of Sociology at Tribhuvan University. However, these conversations do not assert a definitive outcome but presents potential avenues for readers to consider the plausibility of South Asian sociology becoming a reality in the near future. Instead, I plea for a dialogic space among sociologists across South Asia as the rudimentary step for building up South Asian sociological imagination and call for reorienting our disciplinary imagination in tune with the newly emerging forms of interaction between communities and cultures across state structures.